Understanding academic performance based on gender, race, stress and sleep quality - Mok, Eugenie Yen Ling (Universiti Malaysia Sarawak (UNIMAS), 2019)
This study aims to explore gender, race, stress and sleep quality as factors which influence the academic performance of undergraduate students. The samples of study involved 80 students from the Faculty of Cognitive Science and Human Development, Universiti Malaysia Sarawak. The research instrument which will be used in data collection is via questionnaire which consists of demographic information, stress questionnaire (Student Stress Inventory (SSI)) and sleep quality questionnaire (Pittsburgh Sleep Quality Index (PSQI)). The academic performance of the undergraduate students in this study is measured by their cumulative grade point average (CGPA). The result of the study shows that female students performed better than male students; whilst non-Bumiputera students performed better than Bumiputera students. The study also found that the higher the stress level of a student (SSI score), the lower his or her CGPA results. Moreover, the findings showed that there is a significant difference in FCSHD undergraduates' academic performance based on their sleep quality, in which the mean of CGPA for students with good sleep quality is higher than that of students with bad sleep quality. Several limitations were encountered in this study as well, including failure to generalise the findings of the study to represent the whole population of university students and usage of questionnaires. These limitations can be overcome through careful procedures and other methods.